Subjective Assessment of Concert Halls: a Common Vocabulary for Music Lovers and Acousticians - Alicia GIMENEZ; Rosa Marıa CIBRIAN; Salvador CERDA (Archives of Acoustics)
In recent years we have interviewed members of the audience after musical performances and asked them to evaluate the acoustics of the concert halls. A group of ‘music lovers’ (with a high level of musical training and experience) and ‘acousticians’ (with a wide knowledge of the physical characteristics of sound transmission) also attended each performance and answered the same questions as the general public. This group thereby served as a control group when evaluating surveys of the general public. In this paper, the results obtained when analyzing these control group surveys are presented. This analysis shows that a common vocabulary exists between music lovers and acousticians when rating a hall, although the grouping of the questions for each factor depends on the training of the respondents.